Risks and security of internet and systems : 9th International Conference, CRiSIS 2014, Trento, Italy, August 27-29, 2014. Revised selected papers /: 9th International Conference, CRiSIS 2014, Trento, Italy, August 27-29, 2014. Revised selected papers. (2015) - Unknown
No abstract available